Annual Plan 1976-77 Draft Proposals (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1976)
One more town besides undertaking improvement work in other towns. With the same amount provided in 1975-76, it is proposed to cover 2 more towns for water supply facilities and 2 towns for sewerage, thus bringing the total number of towns covered with water supply facilities to 65 and under sewerage to 27.
Planning Department, Haryana Government.